2017
DOI: 10.1101/199240
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Riboglow: a multicolor riboswitch-based platform for live cell imaging of mRNA and small non-coding RNA in mammalian cells

Abstract: RNAs directly regulate a vast array of cellular processes, emphasizing the need for robust approaches to fluorescently tag and track RNAs in living cells. Here, we develop an RNA imaging platform using the Cobalamin (Cbl) riboswitch as an RNA aptamer and a series of probes containing Cbl as a fluorescent quencher linked to a range of fluorophores. We demonstrate fluorescence turn-on upon RNA binding and proof of concept for tracking both mRNA and small U RNA in live cells. Main textThe complex spatiotemporal d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(16 citation statements)
references
References 70 publications
3
13
0
Order By: Relevance
“…2). 14,16,17 In our proof-of-concept study for Riboglow-FLIM in live cells, we showed compatibility with RNA multiplexing by exploiting the phylogenetic diversity of Cbl riboswitches. 20 We recently expanded the system to demonstrate the potential of Riboglow-FLIM for RNA visualization in complex multicellular systems.…”
Section: Introductionmentioning
confidence: 87%
See 4 more Smart Citations
“…2). 14,16,17 In our proof-of-concept study for Riboglow-FLIM in live cells, we showed compatibility with RNA multiplexing by exploiting the phylogenetic diversity of Cbl riboswitches. 20 We recently expanded the system to demonstrate the potential of Riboglow-FLIM for RNA visualization in complex multicellular systems.…”
Section: Introductionmentioning
confidence: 87%
“…To complement existing tools, we developed Riboglow 14,15 and recently expanded the platform to visualize model RNAs in commonly investigated U-2 OS cells using fluorescence lifetime imaging microscopy (FLIM). 16,17 The components of Riboglow are a genetically encoded RNA tag and a small molecule consisting of the ligand cobalamin (Cbl) that is synthetically coupled to a fluorophore (here, ATTO 590 or Cy5).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations